Alimentação escolar e agricultura familiar: a viabilidade da aplicação da lei federal 11.947 de 2009 sob o ponto de vista de diferentes atores sociais - Silva, Denise Boito Pereira da [UNESP] (2014)
Federal Law 11,947 from June 2009 deals with school feeding, and its Article 14 states that 30% of transfers for school meals should be spent on purchasing food from family farmers. Different actors act in this process, with particular emphasis on: family farmers, public managers and technical workers. Each of these actors act differently in the purchase of food products from the family agriculture. But these various actions are interconnected and often depend on each other. It is intended to assess the vision of some of these actors about the implementation of Article 14 in the municipalities of São Paulo, comprising: praise, criticism, suggestions and problems. The basic source of data are surveys and the minutes of discussion groups raised in the Workshop School Feeding and Family Agriculture: Law Enforcement 11.947/2009 in São Paulo, held June 21st and 22nd in 2011 in Jaboticabal (SP). It's possible to realize that there is a difference of the standpoint among the actors involved in the process and the need for greater dialogue and cooperation between them